Problematika Pembelajaran Pendidikan Agama Islam Pada Peserta Didik - Tasurun Amma; Ari Setiyanto; Mahmud Fauzi (Edification Journal : Pendidikan Agama Islam, 2021)
Learning is an interaction between students and their environment, the purpose is a changes behavior for the better. Creating quality learning has many obstacles, mainly; the problem of learning objectives, materials, teachers, students, methods, media, infrastructure, and evaluation. Islamic Education Learning in Students there are three factors, the factors are Internal factors of students, institutional factors, and external factors. Solutions were made to solve the problems that occurred; provide guidance, added the values of the Islamic Religious Education subject, improving the ability of teachers, service, and activating community relations teacher and parent.